A Study on the Induction of Multi-Type Immune Responses in Mice via an mRNA Vaccine Based on Hemagglutinin and Neuraminidase Antigen - Mengyuan Liu; Yixuan Liu; Shaohui Song; Qiurong Qiao; Jing Liu; Yun Xie; Jian Zhou; Guoyang Liao (Vaccines)
Background: The Influenza A virus (IAV), a pathogen affecting the respiratory system, represents a major risk to public health worldwide. Immunization remains the foremost strategy to control the transmission of IAV. The virus has two primary antigens: hemagglutinin (HA) and neuraminidase (NA). Our previous studies have demonstrated that an IAV NA mRNA vaccine can induce Th1-type immune responses in mice. This research examined the immune responses elicited by an mRNA vaccine targeting both HA and NA antigens in murine models. Methods: In this study, we used two dual-antigen immunization strategies: single-site immunization with an IAV HA+NA mRNA vaccine and multi-site immunization with an IAV HA mRNA vaccine and IAV NA mRNA vaccine. Hemagglutination-inhibiting antibody titer and neutralizing antibody titer in the sera of immunized mice were evaluated, and a viral challenge experiment was conducted. Additionally, the immune responses elicited by the two immunization strategies were characterized using flow cytometry and ELISA. Comparative analyses were performed with mice immunized individually with the IAV HA mRNA vaccine, IAV NA mRNA vaccine, and inactivated vaccine. Results: The results showed that by using a multi-site immunization strategy, mice were able to generate higher levels of hemagglutination-inhibiting and neutralizing antibodies, and were protected in a viral challenge experiment. Moreover, the multi-site regimen also promoted the generation of cytotoxic T cells and maintained a balanced Th1/Th2 immune response. Conclusions: Using mRNA vaccine based on a HA and NA antigen with multi-site immunization strategy can induce higher levels of hemagglutination-inhibiting and neutralizing antibodies, and multi-type immune responses in mice, providing new theoretical and experimental support for advancing upcoming influenza vaccines.